Budaya Keselamatan Pasien Terhadap Keselamatan Pasien Rumah Sakit : Tinjauan Pustaka - Hendri, Kevin; Anggileo Pramesona, Bayu; Ganda Ratna, Maya; Lisiswanti, Rika (Medula, 2025)
Patient safety culture is an important aspect of healthcare that focuses on risk reduction and improved patient safety. Patient safety goals are efforts to prevent incidents that can harm patients and health institutions that are designed to improve patient safety by reducing the risk of injury, error, or danger during the provision of health services. Patient safety goals have six points including correct patient identification, effective communication, safety of medications that must be watched out, ensuring the correct surgical site, correct procedures and correct patients, reducing the risk of infection due to health care and reducing the risk of patients falling. Factors that affect patient safety culture include communication, lifelong learning, working hours and occupational safety culture affecting patient safety. Things that greatly contribute to the patient safety culture include openness in communication (67.54%), cooperation in hospital units (67.48%), organizational learning and sustainable development (66.90%) and non-punitive responses in case of mistakes (65.07%).  The conclusion of this study is that all units have a role in patient safety. Patient safety culture and patient safety goals are very closely related to patient safety in hospitals. However, further research is needed related to other factors that affect patient safety culture, especially regarding family involvement in patient safety.